Social Media Application Support Management of Human Resource in Business - Sintani, Lelo; Supardi, Supardi; Albar, Fauzan Manafi; Tanjung, Rona; Lestantri, Indah Dwi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Teenagers and students favor this social media application to make friends and share their life stories. With its various exciting applications, this social media application has attracted professionals in running a business, significantly to improve the quality of life of their human resources. We have proven the truth and error of this assumption by examining literature sources from various domestic and international publications that discuss the advantages and disadvantages of social media in supporting the improvement of human resources among the public. Our data is analyzed using a phenomenological approach, exploring as much data as possible. We analyze it by involving an interpretation coding system in concluding according to the purpose of this study which aims to get the broadest understanding of how social media applications can help improve the quality of human resources. Based on data and scientific evidence, we can report that social media is increasingly being used not only for friendship but also to increase the quality of the company's human resources. Hopefully, this finding will be essential in improving human resources through social media applications.